Using Carboxymethyl Cellulose as the Additive With Enzyme-Catalyzed Carboxylated Starch to Prepare the Film With Enhanced Mechanical and Hydrophobic Properties - Liu, Can; Qin, Shijiao; Xie, Jin; Lin, Xu; Zheng, Yunwu; Yang, Jing; Kan, Huan; Shi, Zhengjun (Frontiers in Bioengineering and Biotechnology, 2021)
Carboxymethyl cellulose, a hydrophobic derivative from cellulose that can be prepared from different biomass, has been widely applied in food, medicine, chemical, and other industries. In this work, carboxymethyl cellulose was used as the additive to improve the hydrophobicity and strength of carboxylated starch film, which is prepared from starch catalyzed by bio-α-amylase. This study investigated the effects of different bio-α-amylase dosages (starch 0.5%, starch 1%) and different activation times (10, 30 min) on starch to prepare the carboxylated starch. The effects of different carboxymethyl cellulose content on the carboxylated starch film were investigated by analysis viscosity, fourier-transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry, x-ray powder diffraction, scanning electron microscope, and contact angle. The results showed that preparing carboxylated starch using activated starch increased the carboxyl content, which could improve the effectiveness of the activated enzyme compared to prolonging the activation time. The carboxyl starch prepared by enzyme catalysis had a lower gelatinization temperature, and enzyme activation destroyed the crystallization area of the starch, thus facilitating the carboxylation reaction. The addition of 15% carboxymethyl cellulose improved the mechanical properties of the prepared film with maximum tensile strength of 44.8 MPa. Carboxymethyl cellulose effectively improved the hydrophobicity of the starch film with the addition amount of 10–30%, while hydrophobic property was stable at 66.8° when the addition amount was exceeded to 35%. In this work, it can be found that carboxymethyl cellulose improve the mechanical and hydrophobic properties of starch film, laying the foundation for the application of carboxylated starch materials.